IDENTITAS BUDAYA DALAM KOMUNIKASI ANTAR-BUDAYA: Kasus Etnik Madura dan Etnik Dayak - Iskandar, Dadan (Jurnal Masyarakat dan Budaya, 2004)
As nation which multiethnic, Indonesia has potency of conflict. From perspective of intercultural communications, inter-ethnic conflict can initiate from cultural identity differences which communicated ethnocentrism. Analyse for ethnical conflict of Dayak and Madura in West Kalimantan show that stereotype - representing the part of self perception through ascription process - as most potential property of cultural identity that generate internal issue in intercultural communications. This Stereotype was afirmed through conflict historically and culturally developed; built by both bloodthirsty tradition "carok" of Madura and "red mug" of Dayak. In order to intercultural communications yield effective intercultural interaction, hence stereotype have to be avoided exposed oneselfly to things actual which is being faced, conflict history should be closed, and the both parties have to assume that communications can assist to finish their problem. Empathy must be opened by both parties to measure communications situation freshment. Equality should be found and developed, as far as that facilitate the solving of problem. If even also still there are difference, hence the oppressive must remain to be avoided.